THE EFFECT OF ROLE STRESS AND JOB RESOURCES ON EMOTIONAL EXHAUSTION WITH WORK-FAMILY CONFLICT MEDIATION AMONG HIGHER EDUCATIONAL STAFF - Kusnani Sita Handayu; Maharani, Anita; Endah Riana, Kurnia (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2025)
This study investigates how role stress and job resources affect emotional exhaustion among university staff, with work-family conflict as a mediator. Using a quantitative causal design, data was collected via 5-point Likert scale questionnaires from 200 employees at XYZ University (from a population of 1,944), including civil servants, permanent staff, and contract workers. SEM-PLS analysis (SmartPLS 3) yielded key findings, role stress significantly increases emotional exhaustion, job resources reduce exhaustion, but not significantly, work-family conflict significantly worsens exhaustion, role stress directly heightens work-family conflict, Job resources weakly reduce work-family conflict (insignificant), Work-family conflict mediates role stress's impact on exhaustion, No significant mediation occurred between job resources and exhaustion. The results highlight that while workplace pressures strongly contribute to burnout, existing support systems fail to sufficiently mitigate stress. This suggests XYZ University should redesign workloads to reduce role ambiguity, strengthen institutional support mechanisms, implement work-life balance policies. The study provides empirical evidence on stress dynamics in higher education, though future research should expand sampling for broader applicability.